Therapeutic Treatment Plan Optimization during the COVID-19 Pandemic: A Comprehensive Physicochemical Compatibility Study of Intensive Care Units Selected Drugs - Maria Gloria Tarantini; Stéphanie Ramos; Philippe-Henri Secrétan; Laura Guichard; Lamia Hassani; Agnès Bellanger; Julien Mayaux; Patrick Tilleul; Fadwa El Kouari; Hassane Sadou Yayé (MDPI AG, 2022)
Background: The SARS-CoV-2 pandemic has resulted in a dramatic rise of the demand for medical devices and drugs. In this context, an important shortage of programmable syringe pumps, used to administrate different drugs in intensive care units, was seen. The opportunity of administrating combinations of five intensive care units selected drugs (Sufentanil, Clonidine, Loxapine, Midazolam, and Ketamine) was considered. Methods: The drug mixtures were studied in a pure form or diluted in NaCl 0.9% or G5%. Twenty-six possible combinations of the five drugs were produced in glass vials or polypropylene syringes and stored at 25 °C for 14 days. The LC method was implemented to study drugs combinations in the presence of the degradation products. The clearness and pH were also monitored. Results: All the 26 possible combinations displayed adequate physicochemical stability at 25 °C: at least 3 days and 7 days, respectively, for the dilution in 0.9% NaCl or glucose 5%, and the pure drug products mixtures. Conclusions: The study provided sufficient stability results, covering the medication administration period of at least three days. The combination of more than two drugs offers the advantage of minimizing the individual doses and reduces unwanted side-effects. Hence, this study opens up the possibility of combining the five drugs in one single syringe, which is useful especially under the current circumstances associated with an important shortage of programmable syringe pumps and pharmaceuticals.